Utilizing wood ash as a liming agent for the improvement of soil health and growth of bermudagrass - Abney, Rebecca B.; Fitch, Jack (Frontiers in Soil Science, 2026)
Wood ash is a common by-product of industrial timber and timber product production. It has been used as a soil amendment to increase pH for centuries; however, much of the current industry sends this byproduct to landfills. In this study, we investigated the response of soil properties and bermudagrass (Cynodon dactylon) growth to the addition of ash as a soil amendment. A soil that was previously in agricultural use was amended with wood ash along with five other treatments (lime, fertilizer, lime + fertilizer, ash + fertilizer, and a control with no amendment) at the level of lime equivalency to raise the soil pH from 5.35 to 6.5. Soils were amended with liming treatments (lime and wood ash) and allowed to equilibrate for five months, during which they were planted with bermudagrass, and differences in plant growth and soil physical and chemical properties were monitored. Treatments with ash had the highest overall productivity, with a 2× higher yield than the control treatment in the first cutting, and the largest shifts in soil properties. In particular, there was increased soil carbon (~1% higher with ash amendment compared with other treatments), cation exchange capacity (~2× with ash amendment), and phosphorus and potassium concentrations in treatments with ash compared to non-ash treatments. This type of amendment is generally well-suited for intensively managed or degraded southeastern piedmont agricultural soils that would benefit from an increase in pH, nutrient concentrations, soil organic matter, or overall soil health. We found that using forest waste wood ash as a soil amendment can be an effective strategy to increase soil carbon sequestration, divert waste from landfills, and increase productivity.